Preliminary Study on Worldviews - Sartini Sartini; Heddy Shri Ahimsa-Putra (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
Worldviews are an important part of human life because they illustrate the ways people think and act. This article aims to review studies conducted by scholars, definitions of the term